2009
DOI: 10.1002/adma.200901113
|View full text |Cite
|
Sign up to set email alerts
|

Interface Dynamic Behavior Between a Carbon Nanotube and Metal Electrode

Abstract: The heterointerface between a carbon nanotube (CNT) and a metal is of prime importance for CNT-based nanotechnology.[1] In nanoelectronic circuits, the behavior of every single CNT-based device is highly influenced by the atomic and electronic structures of the contact interface between a nanotube and an electrode. Ohmic CNT/metal contacts of high conductivity are usually prerequisite for the effective performance of an individual device, as well as their interconnections.[2] On the other hand, controlled synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
3
36
2
Order By: Relevance
“…Only after the particle has been melted (or premelted), it absorbs some carbon shells (indicated by a white arrow in figure 4(b)), implying that the diffusion of C into the W particle starts at a high temperature, close to the melting point of the particle (∼ 3400 K). A similar absorption of CNT shells by a tungsten tip was found to result in the formation of hexagonal α-WC [23]. However, our observation contradicts with some other reports.…”
Section: Resultscontrasting
confidence: 57%
“…Only after the particle has been melted (or premelted), it absorbs some carbon shells (indicated by a white arrow in figure 4(b)), implying that the diffusion of C into the W particle starts at a high temperature, close to the melting point of the particle (∼ 3400 K). A similar absorption of CNT shells by a tungsten tip was found to result in the formation of hexagonal α-WC [23]. However, our observation contradicts with some other reports.…”
Section: Resultscontrasting
confidence: 57%
“…24 The formation of metal carbides can significantly reduce the contact resistance at the metal-CNT interface. 19,23 Compared to the vertically aligned CNTs prepared by Bayer et al and Nessim et al, 19,20 we observed a higher value of resistance. We attribute this to the subsequent embedding and planarization processes.…”
contrasting
confidence: 43%
“…Potentially, the formation of a thin intermediate carbide layer causes the significantly reduced contact resistance. 23,24 However, as shown by Leroy et al, 24 carbide formation is inhibited as long as oxygen is present. Thus, carbide formation may occur after annealing the sample with the top metallization, only.…”
Section: Resultsmentioning
confidence: 93%
“…For the case of Au contacts, the melting threshold was similarly at 10 8 A/cm 2 and the open-end CNTs again led to less resistive contacts [ 88 ]. The authors do not discuss chemical mixing of the materials [ 85 ] or hot-spot migration upon annealing [ 79 ].…”
Section: Carbon Nanotubesmentioning
confidence: 92%
“…A two-terminal electrical holder was used to follow the dynamics of a MWCNT-W electrode wire contact interface when exposed to a high current density [ 85 ]. The end-to-end contact established was considerably changed as chemical reactions promoted by joule heating took place between the C and W. The formation of the hexagonal phase α-WC was aided further by electromigration leading to visible extensions of mixing and eventual extrusion of excess carbon from the top of the WC segments.…”
Section: Carbon Nanotubesmentioning
confidence: 99%